Problematika Dan Implementasi Pembelajaran Daring Pada Masa Pandemi Covid-19 - Siti Bariroh; Maulidatul Khuriyah (Fakultas Keguruan dan Ilmu Pendidikan - Universitas Gresik, 2021)
Corona Virus Disease 2019 (COVID-19) is a new type of disease that infects the lungs of sufferers, besides that the Covid-19 virus is also rapidly transmitted only through the air. On March 11, 2020 the World Health Organization (WHO) declared it a pandemic. the government urges the public to work and study from home. Learning done online from home raises various problems that are felt by principals, teachers, students, and parents.This research is a qualitative research. Research that discusses the Problems, Implementation of Online Learning during the Covid-19 Pandemic at MI Asmaiyah Gresik. The purpose of this study is to describe the problems and implementation of online learning faced by teachers, students, and parents during the COVID-19 pandemic. This research was conducted in MI Asmaiyah, Gresik Regency. Data collection techniques used in this study were observation, interviews, and documentation.The results show that 1) The problems faced by students, teachers, and parents are: Problems with internet quotas and students' signals, students are less enthusiastic when participating in online learning, teachers have difficulty managing classes, limitations on facilities and infrastructure owned by students. 2) The implementations that have been carried out by MI Asmaiyah are: Giving free education quotas for students, Teachers holding video calls to students to encourage learning, teachers asking parents for help to be able to work together in supervising children during online learning, using applications that is easy to do online learning, educators at MI Asmaiyah have succeeded in implementing online learning to all students at MI Asmaiyah Gresik.